2015
DOI: 10.1371/journal.ppat.1004788
|View full text |Cite
|
Sign up to set email alerts
|

Hantaan Virus Infection Induces Both Th1 and ThGranzyme B+ Cell Immune Responses That Associated with Viral Control and Clinical Outcome in Humans

Abstract: Hantaviruses infection causing severe emerging diseases with high mortality rates in humans has become public health concern globally. The potential roles of CD4+T cells in viral control have been extensively studied. However, the contribution of CD4+T cells to the host response against Hantaan virus (HTNV) infection remains unclear. Here, based on the T-cell epitopes mapped on HTNV glycoprotein, we studied the effects and characteristics of CD4+T-cell responses in determining the outcome of hemorrhagic fever … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 77 publications
2
44
0
Order By: Relevance
“…This notion is supported by evidence that hantavirus-specific T cells play a critical role in the control of virus infection (17)(18)(19). Our previous results have demonstrated that the T-cell response during the acute stage of HFRS in patients is characterized by vigorous cytotoxic T cell (CTL) responses and multifunctional T helper (Th) cell responses against HTNV infection (20,21). Patients with milder severities of HFRS typically mount vigorous HTNV-specific CD4 + and CD8 + T-cell responses directed against the epitopes of HTNV, whereas patients with severe or critical HFRS tend to have weak and narrowly focused T-cell responses (20)(21)(22).…”
mentioning
confidence: 78%
“…This notion is supported by evidence that hantavirus-specific T cells play a critical role in the control of virus infection (17)(18)(19). Our previous results have demonstrated that the T-cell response during the acute stage of HFRS in patients is characterized by vigorous cytotoxic T cell (CTL) responses and multifunctional T helper (Th) cell responses against HTNV infection (20,21). Patients with milder severities of HFRS typically mount vigorous HTNV-specific CD4 + and CD8 + T-cell responses directed against the epitopes of HTNV, whereas patients with severe or critical HFRS tend to have weak and narrowly focused T-cell responses (20)(21)(22).…”
mentioning
confidence: 78%
“…Screening of CD4 responses with peptide pools derived from the NTNV glycoprotein revealed a subset of virus-specific CD4 cells that expressed GzmB, perforin, and/or CD107a (29). These cells were found at significantly higher frequencies and exhibited greater cytotoxicity among patients with mild/moderate disease compared to those with severe or critical illness.…”
Section: Infections In Which Cd4 Ctl Are Protectivementioning
confidence: 99%
“…Herein, we review the characteristics of CD4 CTL across a range of human viral infections including human immunodeficiency virus type 1 (HIV-1) (911, 1820), CMV (8, 10, 12, 21, 22), Epstein–Barr virus (EBV) (2325), influenza (26, 27), viral hepatitis (28), hantavirus (29), dengue (30–33), and parvovirus B19 (34). CD4 CTL may also be involved more broadly in the regulation of immune responses, through regulatory T cell (Treg) function (to be discussed later) and may also be involved in other non-viral infections and anti-tumor responses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, epitopes of HTNV NP that elicit CD4 + and CD8 + cytotoxic T lymphocyte responses have been extensively studied (Ennis et al, 1997; Van Epps et al, 1999; Lee et al, 2002). Viral GP-specific T cell responses have also been discovered (Ma et al, 2015). Protective immunity elicited through infection with recombinant HTNV-glycoprotein in murine models has also been demonstrated (Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%